CHARACTER OF IMMUNE DISORDERS IN PATIENTS WITH ACUTE PURULENT MAXILLATIS - Popov, N.N.; Ognivenko, E.V.; Romanova, E.A. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The purpose of the research was the study of immune disoders in patients with acute purulent maxillitis, the study of general and local immune reactions before and after treatment. 42 patiennts with acute purulant maxillitis have been studied. They were divided into 2 groups: the 1-st group consisted of 22 patients with maxillitis without complications. The 2-nd group (20 patients) had maxillitis with complications. The acute purulent maxilitis in the 1-group is proceed with local and general immunity factors activation. Patients from 2-nd group didn’t showimmune factors’ activation.